Komunitas dan Preferensi Habitat Gastropoda pada Kedalaman Berbeda di Zona Litoral Danau Singkarak Provinsi Sumatera Barat - Wendri, Yuli; Nurdin, Jabang; Zakaria, Indra Junaidi (Metamorfosa: Journal of Biological Sciences, 2019)
This research was conducted in Lake Singkarak from February to March 2016, using purposive sampling method in three locations namely Tanjung Mutiara, Malalo and Paninggahan, at a depth of 0.5 m, 1 m and 1.5 m in each location. Samples were collected using 30x30 cm 2  surber net. The result showed four gastropod species from family of Thiaridae, namely  Melanoides granifera ,  Melanoides tuberculata ,  Brotia costula  and  Thiara scabra . Average population density of gastropod in Lake Singkarak was 399.75 ind / m 2 . The population density at depths ranging from 271.11 to 568.89 ind/m 2 , the highest population density is showed at a depth of 1.5 m and the lowest at a depth of 0.5 m.  Melanoides tuberculata  shows highest density at all depths.  M. granifera  prefers habitats with a depth of 1.5 m,  M. tuberculata  prefers a depth of 1 m,  T. scabra  prefers a depth up to 1.5 m and  B. Costula  prefer habitat with a depth of 0.5 m. Condition of Lake Singkarak shows as favorable and suitable habitat for gastropod’s life.